The Impact of USAID IUWASH Program on Improving Clean Water and Proper Sanitation in North Sumatra - Anastasya, Millenia Putri; Padmi, Made Fitri (GLOBAL INSIGHT JOURNAL, 2024)
This study aims to analyze the impact of USAID IUWASH programme to the clean water, sanitation and hygiene problems in Indonesia especially in North Sumatera. The United States government country, through USAID distributes aid in the form of grants. This research applies a qualitative research method, the collected data were analyzed using international cooperation theory and Official Development Assistance concept. The results of this study found that the government of Indonesiaalso joined the USAID for increase the clean water, sanitation, and hygiene. The USAID IUWASH programme is effective in improving clean water, sanitation, andhygiene in North Sumatera, referring to the results of the data of USAID IUWASHand interviewee with Regional Manager USAID IUWASH of North Sumatera, headof facilities and infrastructure Bapperida of Simalungun, and local resident of North Sumatera